EFEKTIVITAS DAN DAMPAK PROGRAM NASIONAL PEMBERDAYAAN MASYARAKAT MANDIRI PERDESAAN (PNPM) TERHADAP PENDAPATAN KELUARGA KK MISKIN - Kemenuh, Ida Bagus Adi Mahaputra; Wenagama, I Wayan (E-Jurnal Ekonomi Pembangunan Universitas Udayana; vol.6.No. 9. September 2017(pp.1628-1867), 2017)
ABSTRACT The purpose of this research is to know the effectiveness and impact of national program of rural community empowerment (PNPM) towards family income in Kediri Sub-district of Tabanan Regency. The research was conducted in Kecamatan Kediri of Tabanan Regency. Technique of collecting data with direct record in the form of RTS data in District Kediri Tabanan. The number of samples taken as many as 92 respondents determined using Slovin approach with Probability Sampling technique. Analytical technique used in this research is with multiple regression analysis technique. Based on the analysis results can be concluded the effectiveness of the program and the impact of the implementation of the program significantly influence simultaneously to the family income in Kecamatan Kediri Tabanan District with the value of Fhitung (30,359) greater than Ftable (3.09) with a significance value of 0.000 <0.05. The effectiveness of the program has a positive effect on family income in Kecamatan Kediri, Tabanan regency with tcount = 10,910 bigger than ttable = 1,671. Keywords : PNPM Program Effectiveness, Impact of PNPM Program Implementation, Family Income